"Sticks and Stones May Break My Bones, But Bullying Will Get Me Bangin'": Bullying Involvement and Adolescent Gang Joining. (October 2019) - Shelley, Walter W.; Peterson, Dana
Studies have shown that adolescents' involvement in bullying (as perpetrators, victims, or both) is related to more negative outcomes than noninvolvement, and a small subset of studies has connected bullying to the specific outcome of gang involvement. However, most of these studies have been cross-sectional and have not examined causal pathways by which bullying and gang involvement may be related. Furthermore, some studies find sex differences in prevalence, type, and outcomes of bullying as well as in the relationship between bullying and gang involvement, suggesting important prevention implications, yet this remains under examined. Our study explicitly examines these issues identifying the overlap in bullying outcomes with antecedent gang risk factors, and suggesting potential direct and indirect effects of bullying on gang involvement; we test these relationships, and potential sex differences, using longitudinal data from the second National Evaluation of Gang Resistance Education and Training to overcome limitations of prior research. Consistent with our expectations, we find that (1) bully-victims exhibit the highest levels of risk; (2) bullies, victims, and bully-victims have increased odds of later gang joining, compared to uninvolved youth; (3) the inclusion of risk factors partially mediates the effect of bullying involvement on gang onset for bullies and victims and fully mediates the effect for bully-victims; and (4) some evidence of sex differences exists. Given these insights, greater connections between bullying and gang prevention efforts may be worthwhile.